Ecological construction design and planning based on energy-saving building technology. (20th September 2022) - Cheng, Xiaoting
When designing buildings, especially eco-energy-saving buildings, we should fully consider their functions and characteristics, determine the existence of forms by function, and combine building technology with architectural art, instead of blindly pursuing visual impact or even grandstanding and manufacturing products that do not conform to scientific laws, which will increase energy consumption and reduce comfort. This paper builds an ecological construction design and planning system based on energy-saving building technology. When constructing a framework for smart construction of eco-energy-saving buildings, based on the information processing process, this paper proposes an integrated framework system that integrates smart construction requirements and various technical characteristics. Finally, this paper conducts system verification through experimental research. The research results show that the ecological construction planning and design system based on energy-saving building technology constructed in this paper can effectively improve the effect of ecological construction design and planning.